Site and plant community parameters drive the effect of vegetation on litterfall and nutrient inputs in restored tropical forests - Machado, Deivid L. [UNESP]; Engel, Vera L. [UNESP]; Podadera, Diego S. [UNESP]; Sato, Luciane M. [UNESP]; Goede, Ron G. M. de; Moraes, Luiz F. D. de; Parrotta, John A. (Springer, 2021)
Background and aims Restoring healthy ecosystem depends on recovering not only biodiversity, but also ecosystem processes and functionality. We investigated the effects of tree community parameters and site abiotic conditions on nutrient cycling in restored forests. Methods We assessed litter production and nutrient inputs in five 16-year old restored forests established using different restoration methods and species combinations, i.e. unplanted control (natural regeneration), direct seeding, agroforestry, mixed commercial species plantation (commercial mix), and high-diversity plantation, replicated at two sites that differed in soil fertility. We used adjacent seasonal semideciduous forest remnants as references. Results Restoration treatments with intermediate and high species richness had higher litter and nutrient inputs and did not differ from the reference forest. In the more fertile site, litter and nutrient inputs increased across different treatments with increasing stand density, whereas in the low fertility site, litter and nutrient inputs in the different treatments increased with increasing tree species richness and the proportion of putative nitrogen-fixing tree species. Conclusions Restoration treatments, even those with low species richness, but with a relatively high proportion of trees with nitrogen-fixing capability might be effective in restoring nutrient cycles in lower fertility soils, whereas in the more fertile soils it is possible to increase nutrient inputs by establishing restoration treatments at high stem densities. Our results suggest that the magnitude of relationships among plant community parameters and nutrient cycling depends strongly on site conditions.
Keywords: Nutrient cycling; Ecological restoration; Tropical seasonal forest; Species richness; Nitrogen-fixing tree; Litterfall; Atlantic forest